Cave water walker: an extremely troglomorphic Troglaphorura gladiator gen. et sp. nov. (Collembola, Onychiuridae) from Snezhnaya Cave in the Caucasus - Vargovitsh, Robert S. (Zootaxa, 2019)
A new springtail genus and species of the family Onychiuridae, Troglaphorura gladiator gen. et sp. nov., is described from deep Snezhnaya (Snow) Cave System (-1760 m) in the West Caucasus. Postantennal organ with only a single unlobed vesicle, sense organ of third antennal segment with sensory rods of complex structure, foot complex with missing empodia and extremely long thin claws as well as relatively long appendages, primitive dorsal chaetotaxy and presence of 1+1 pseudocelli on the head posterior part are extraordinary characters within the family but diagnostic for new genus and species. Extreme troglomorphy of new species is discussed. It was sampled in epineustonic habitats in bottom part of the cave and represents a genuine example of troglomorphic neustonic and hygropetric collembolan life form—a cave water walker.